An analysis of cause-specific under-5 mortality in Bangladesh using the demographic and health survey 2011 and 2017–2018 - Tapas Mazumder; Itismita Mohanty; Danish Ahmad; Theo Niyonsenga (BMC Pediatrics, 2024)
Abstract Background As the Sustainable Development Goal 3.2.1 deadline (2030) approaches, rapidly reducing under-5 mortality (U5M) gains more prominence. However, initiatives or interventions that aided Bangladesh in achieving Millennium Development Goal 4 showed varied effectiveness in reducing certain cause-specific U5M. Therefore, this study aimed to examine the predictors of the key cause-specific mortalities. Methods This cross-sectional study was conducted using the Bangladesh Demographic and Health Survey 2011 and 2017-18 data. Cause-specific U5M was examined using multilevel multinomial mixed-effects analyses, and overall/all-cause U5M was examined using multilevel mixed-effects analyses. The respective estimates were compared. Results The cause-specific analysis revealed that pneumonia and prematurity-related U5M were significantly associated with antenatal care and postnatal care, respectively. However, analysis of overall/all-cause U5M did not reveal any significant association with health services. Twins or multiples had a greater risk of mortality from preterm-related conditions (adjusted Relative Risk Ratio (aRRR): 38.01, 95% CI: 19.08–75.7, p < .001), birth asphyxia (aRRR: 6.52, 95% CI: 2.51–16.91, p < .001), and possible serious infections (aRRR: 11.12, 95% CI: 4.52–27.36, p < .001) than singletons. Children born to mothers 18 years or younger also exhibited a greater risk of mortality from these three causes than children born to older mothers. This study also revealed an increase in the predicted risk of prematurity-related mortality in the 2017-18 survey among children born to mothers 18 years or younger, children born to mothers without any formal education, twins or multiples and children who did not receive postnatal care. Conclusions This research provides valuable insights into accelerating U5M reduction; a higher risk of preterm-related death among twins underscores the importance of careful monitoring of mothers pregnant with twins or multiples through the continuum of care; elevated risk of death among children who did not receive postnatal care, or whose mothers did not receive antenatal care stresses the need to strengthen the coverage and quality of maternal and neonatal health care; furthermore, higher risks of preterm-related deaths among the children of mothers with low formal education or children born to mothers 18 years or younger highlight the importance of more comprehensive initiatives to promote maternal education and prevent adolescent pregnancy.